Розрахунок міцності бетонних литої і пакетованої охоронних смуг - Круковський, О. П.; Курносов, С. А.; Макеєв, С. Ю.; Стадничук, М. М. (My University, 2023)
Встановлено вагомість впливу на межу міцності бетонної смуги кожного з факторів, що утворюють ризик її руйнування. При цьому враховані діапазони зміни цих факторів. Найбільший вплив (до 33%) здійснює фактор потужності вугільного пласта km.

The importance of the impact on the strength limit of the concrete wall of each of the factors that create the risk of its destruction has been established. At the same time, the ranges of change of these factors are considered. The largest influence (up to 33%) is exerted by the coal seam capacity factor km.
Calculation of the strength of cast and packaged concrete protective walls
Keywords: повторне використання дільничних виробок; засоби охорони виробок; швидкотвердіючі суміші; параметри литих і пакетованих охоронних смуг; інтенсивність навантаження засобів охорони; re-use of development workings; means of workings protection; quick-setting mixtures; parameters of cast and packaged protective walls; load intensity of protective means